Low within‐ and between‐day variability in exposure to new insulin glargine 300 U/ml. Issue 3 (7th January 2015) - Becker, R. H. A.; Nowotny, I.; Teichert, L.; Bergmann, K.; Kapitza, C.
<x xml:space="preserve">Abstract</x> Aims To characterize the variability in exposure and metabolic effect of insulin glargine 300 U/ml (Gla‐300) at steady state in people with type 1 diabetes (T1DM). Methods A total of 50 participants with T1DM underwent two 24‐h euglycaemic clamps in steady‐state conditions after six once‐daily administrations of 0.4 U/kg Gla‐300 in a double‐blind, randomized, two‐treatment, two‐period, crossover clamp study. Participants were randomized to receive Gla‐300 as a standard cartridge formulation in the first treatment period, and as a formulation with enhanced stability through polysorbate‐20 addition in the second treatment period, or vice versa. This design allowed the assessment of bioequivalence between formulations and, subsequently, within‐ and between‐day variability. Results The cumulative exposure and effect of Gla‐300 developed linearly over 24 h, and were evenly distributed across 6‐ and 12‐h intervals. Diurnal fluctuation in exposure (within‐day variability) was low; the peak‐to‐trough ratio of insulin concentration profiles was <2, and both the swing and peak‐to‐trough fluctuation were <1. Day‐to‐day reproducibility of exposure was high: the between‐day within‐subject coefficients of variation for total systemic exposure (area under the serum insulin glargine concentration time curve from time 0 to 24 h after dosing) and maximum insulin concentration were 17.4% [95% confidence interval (CI) 15–21] and 33.4% (95% CI 28–41), respectively. Reproducibility of the metabolic effect was lower than that of exposure. Conclusions Gla‐300 provides predictable, evenly distributed 24‐h coverage as a result of low fluctuation and high reproducibility in insulin exposure, and appears suitable for effective basal insulin use.